2016
DOI: 10.1080/09168451.2016.1184560
|View full text |Cite
|
Sign up to set email alerts
|

Delphinidin prevents disuse muscle atrophy and reduces stress-related gene expression

Abstract: Delphinidin is a member of the anthocyanidin class of plant pigments. We examined the effects of delphinidin on muscle atrophy. Oral administration of delphinidin suppressed the muscle weight loss induced by mechanical unloading. Microarray analysis showed that delphinidin suppresses the upregulation of oxidative stress-related gene expression, including the expression of Cbl-b. Thus, delphinidin may prevent unloading-mediated muscle atrophy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 25 publications
4
19
0
Order By: Relevance
“…Here we report a significant increase in the mRNA levels of Cbl-b in the soleus muscle of the unloaded animals that was completely prevented by allopurinol. Cbl-b-deficient mice are resistant to unloading-induced atrophy 11 and its inhibition with delphinidin (an anthocyanin), suppresses the atrophy of skeletal muscle in a rodent model of disuse 51 . IRS-1 is the docking protein for the regulatory subunit of PI-3K, the kinase that activates Akt.…”
Section: Discussionmentioning
confidence: 99%
“…Here we report a significant increase in the mRNA levels of Cbl-b in the soleus muscle of the unloaded animals that was completely prevented by allopurinol. Cbl-b-deficient mice are resistant to unloading-induced atrophy 11 and its inhibition with delphinidin (an anthocyanin), suppresses the atrophy of skeletal muscle in a rodent model of disuse 51 . IRS-1 is the docking protein for the regulatory subunit of PI-3K, the kinase that activates Akt.…”
Section: Discussionmentioning
confidence: 99%
“…Delphinidin is found in pigmented fruits and vegetables and confers a blue-red color (Murata et al, 2016). Two studies have suggested that delphinidin prevents muscle atrophy by characterizing its underlying mechanisms (Murata et al, 2016;.…”
Section: Delphinidinmentioning
confidence: 99%
“…Delphinidin is found in pigmented fruits and vegetables and confers a blue-red color (Murata et al, 2016). Two studies have suggested that delphinidin prevents muscle atrophy by characterizing its underlying mechanisms (Murata et al, 2016;. Delphinidin significantly reversed MuRF1 expression by upregulating the nuclear factor of activated T cells 3 (NFATc3) and miR-23a (Murata et al, 2017).…”
Section: Delphinidinmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, the increased expression of Nox4 was found in m. quadriceps femoris of 10-day tailsuspended mice [68].…”
Section: Discussionmentioning
confidence: 87%